Student satisfaction as a performance indicator of higher education institution - Nastasić, Aleksandra (Mednarodno inovativno poslovanje, 2019)
Modern performance measurement systems include customer satisfaction as an important performance indicator. From the standpoint of the Higher Education Institution (hereinafter HEI) in Serbia, key performance indicators are quality indicators used to assess the current situation; to identify service failures and to take on service recovery; to improve total quality of the institution and to determine the future development of the institution. In increasingly competitive and dynamic educational environment, the management of a HEI is aware of the importance of student satisfaction in the context of student motivation and retention, recommendations to potential freshmen, recruiting efforts and funding, as well as performance management.
Keywords: educational process; higher education; izobraževalni proces; kazalniki uspešnosti; nepedagoška podpora; non-teaching suppor; performance indicators; student satisfaction; visokošolska izobrazba; zadovoljstvo študentov